Mechanosensing at the Nuclear Envelope by Nuclear Pore Complex Stretch Activation and Its Effect in Physiology and Pathology - Donnaloja, F.; Jacchetti, E.; Soncini, M.; Raimondi, M. T. (Frontiers in Physiology, 2019)
Cell fate is correlated to mechanotransduction, in which forces transmitted by the cytoskeleton filaments alter the nuclear shape, affecting transcription factor import/export, cells transcription activity and chromatin distribution. There is in fact evidence that stem cells cultured in 3D environments mimicking the native niche are able to maintain their stemness or modulate their cellular function. However, the molecular and biophysical mechanisms underlying cellular mechanosensing are still largely unclear. The propagation of mechanical stimuli via a direct pathway from cell membrane integrins to SUN proteins residing in the nuclear envelop has been demonstrated, but we suggest that the cells’ fate is mainly affected by the force distribution at the nuclear envelope level, where the SUN protein transmits the stimuli via its mechanical connection to several cell structures such as chromatin, lamina and the nuclear pore complex (NPC). In this review, we analyze the NPC structure and organization, which have not as yet been fully investigated, and its plausible involvement in cell fate. NPC is a multiprotein complex that spans the nuclear envelope, and is involved in several key cellular processes such as bidirectional nucleocytoplasmic exchange, cell cycle regulation, kinetochore organization, and regulation of gene expression. As several connections between the NPC and the nuclear envelope, chromatin and other transmembrane proteins have been identified, it is reasonable to suppose that nuclear deformations can alter the NPC structure. We provide evidence that the transmission of mechanical forces significantly affects the basket conformation via the Nup153-SUN connection, both altering the passage of molecules through it and influencing the state of chromatin packing. Finally, we review the known correlations between a pathological NPC structure and diseases such as cancer, autoimmune disease, aging and laminopathies.